(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Migration is the movement of people from one location to another with the goal of settling, either permanently or temporarily, in a new site. This form of mobility could be from one country to another or between states of a country, such as rural-rural, rural-urban, urban-urban, or urban-rural. Individuals can migrate individually, as a family unit, or in huge numbers. A refugee is someone who is forced to relocate from their home to another location due to a natural disaster or civil conflict. Migrants continue to struggle to integrate fully into society’s economic, cultural, social, and political lives. This paper attempts to examine the reasons and nature of migration.